The modern Indonesian experience in coexistence between Muslims and others: presentation and evaluation - Zaim, Muntaha Artalim (Universitas Islam Negeri Alauddin Makassar, 2024)
Abstract The purpose of this paper is to explore and evaluate Indonesia's modern experience in promoting peaceful coexistence between Muslims and others. The main issue addressed by the research is how to achieve a balance between preserving the country's Islamic identity and ensuring the rights of non-Muslim minorities, amid contemporary social and political challenges. The research relies on an analytical and descriptive methodology, presenting historical and social facts and events that have contributed to shaping the coexistence model in Indonesia. The findings indicate that the Islamic identity remains preserved, despite intellectual skirmishes. The main contribution of the research lies in its recommendations for future policies that can help enhance this coexistence at the national and international levels. The final results affirm that Indonesia is an inspiring model that can be utilized by other countries seeking to promote peaceful coexistence among their diverse societal components, though some of these experiences require assessment and adjustment.